Obese mice induced by high-fat diet have differential expression of circular RNAs involved in endoplasmic reticulum stress and neuronal synaptic plasticity of hippocampus leading to obesity-associated cognitive impairment - Niu, Yan; Chang, Pan; Liu, Tian; Shen, Xi; Zhao, Hui; Zhang, Mingxia; Lei, Shengping; Chen, Baoying; Yu, Jun (Frontiers in Molecular Neuroscience, 2022)
Obesity induced by a high-fat diet (HFD) is an important cause of impaired memory and cognitive function, but the underlying mechanisms are not clear. In the present study, we analyzed the levels of circRNAs in the hippocampus of C57BL/6J mice and evaluated the memory and cognition ability of C57BL/6J mice with HFD using Morris water maze and Y-maze approaches to explore the potential mechanisms linking circRNAs in obesity-associated cognitive impairment. Learning performance showed that HFD-induced obesity mice have impaired memory and cognition. The Arraystar analysis of the hippocampus displayed that HFD-induced obesity leads to the differential expression of circRNAs (DE-circRNAs) in mice. In total, 46 circular RNAs with elevated expression and 10 with decreased expression were identified. Among them, mmu_circRNA_004797 was identified to be significantly downregulated and the expression of mmu_circRNA_21040 was significantly upregulated in the HFD-fed mice, compared with control mice by PCR test. Bioinformatics analysis also showed that the upregulated circRNAs were related to the neuronal function and behavior, and material transport process, while downregulated circRNAs participated in the process of cell response to external stimuli, such as cellular response to nutrient levels. Furthermore, the KEGG pathway analysis showed that the upregulated circRNAs are mainly involved in Axon guidance, calcium signaling pathway, and ErbB signaling pathway. Only a single significant pathway, that is, “protein processing in endoplasmic reticulum”, was observed in the downregulated circRNAs. Finally, we examined the deficits of hippocampal synaptic plasticity and detected the expression of ER stress-related protein. The results showed that ER stress was activated in the hippocampus, and hippocampal synaptic plasticity deficits were displayed. Our results demonstrated that circRNAs were most likely implicated in the predisposition to obesity-associated cognitive impairment.